Fatty acid 2-hydroxylase facilitates rotavirus uncoating and endosomal escape - Enkai Li; Ruochen Zang; Takahiro Kawagishi; Wei Zhang; Kruthika Iyer; Gaopeng Hou; Qiru Zeng; Rita M. Meganck; Susan R. Ross; Xin Wang; Xiong Su; Siyuan Ding (Proceedings of the National Academy of Sciences, 2025)
Despite the clinical significance of many nonenveloped viruses, the molecular mechanisms of their internalization and membrane penetration are not well understood. Rotaviruses (RVs) are nonenveloped double-stranded RNA viruses and the leading cause of severe dehydrating diarrhea in infants and young children. We identified fatty acid 2-hydroxylase (encoded by FA2H ) in the fatty acid 2-hydroxylation pathway as a proviral gene that supports RV infection. Genetic ablation of FA2H interfered with an early step in RV entry for multiple human and animal strains. Intestinal epithelial cell–specific deletion of Fa2h limited RV replication and diarrhea incidence in vivo. Using transmission electron microscopy and immunofluorescence, we found that viral particles were trapped in early and late endosomes in FA2H knockout cells, preventing their further exit into the cytosol. The defect in RV infectivity could be partially restored by treatment of cells with long-chain 2-hydroxy ceramides or a calcium channel activator that promotes Ca 2+ efflux from endosomes. Both Junín virus, an arenavirus, and Shiga toxin, dependent on endosomal Ca 2+ transport, required FA2H for efficient entry. Together, this study highlights a role of fatty acid 2-hydroxylation in RV entry into host cells and implicates 2-hydroxy ceramides as potential key regulators of endosomal Ca 2+ levels, offering important insights for the development of host-directed therapies targeting fatty acid 2-hydroxylation to control microbial infections.